Can Family Financial Resources Buy Friends?: Family Financial Resources and Friendship Patterns Among Migrant Workers in China. (August 2015) - Fong, Eric; Tong, Yuying
This study examines empirically the relationship between the economic conditions back home and the friendship patterns of migrants at the new destination. The migrant adjustment process is not just associated with the individual socioeconomic status, but is also related to family economic conditions in their place of origin. Our study, based on data collected in 2010 on migrant workers in seven cities located in Pearl River Delta and Yangzi River Delta in China, confirms the relationship. Our findings indicate that rural migrants in China with higher income and better economic conditions back home are associated with more friends in the host society. We also find friendship patterns to be different between male and female migrant workers. In particular, family economic conditions back home are particularly important for males' friendship pattern, but not for females. Implications of the findings are discussed.